2014
DOI: 10.1016/j.tcb.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: an emerging link between gene regulation and nuclear organization

Abstract: Mammalian genomes encode thousands of long non-coding RNAs (lncRNAs) that play important roles in diverse biological processes. As a class, lncRNAs are generally enriched in the nucleus and specifically within the chromatin-associated fraction. Consistent with their localization, many lncRNAs have been implicated in the regulation of gene expression and in shaping three-dimensional nuclear organization. Here, we discuss the evidence that many nuclear-retained lncRNAs can interact with various chromatin regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
229
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(233 citation statements)
references
References 136 publications
(259 reference statements)
2
229
0
2
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are enriched within the chromatin-associated fraction, and many have been implicated in the recruitment of chromatin-modifying complexes, such as polycomb repressive complex 2 (PRC2), as well as 3D nuclear organisation [51]. Using the iCLIP assay, we have found that SAFB1 binds to several lncRNA transcripts (MALAT1, NEAT1, TUG1 and XIST), which have been linked to regulation of gene expression [43].…”
Section: Binding To Non-coding Rnamentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are enriched within the chromatin-associated fraction, and many have been implicated in the recruitment of chromatin-modifying complexes, such as polycomb repressive complex 2 (PRC2), as well as 3D nuclear organisation [51]. Using the iCLIP assay, we have found that SAFB1 binds to several lncRNA transcripts (MALAT1, NEAT1, TUG1 and XIST), which have been linked to regulation of gene expression [43].…”
Section: Binding To Non-coding Rnamentioning
confidence: 99%
“…74 In fact, functional studies have revealed that lncRNAs participate in a variety of biological processes, including transcriptional regulation by recruiting chromatin regulatory proteins to specific genomic locations, genomic imprinting, organization of protein complexes, and shaping distinct nuclear structures. 75,76 Recent RNA sequencing studies in mouse and human hearts revealed that lncRNAs are dynamically regulated during disease. 11,[77][78][79] In human hearts, a total number of 18 480 lncRNAs were detected, of which ≈600 were differentially expressed in failing hearts with either ischemic or non-ischemic origin.…”
Section: Lncrnas As New Players In Cardiac Biologymentioning
confidence: 99%
“…113 Both Bvht and Fendrr seem to interact with PRC2 to regulate target gene expression during cardiac development. 46,47 Bvht was shown to interact with the catalytic SUZ12 component of PRC2 by in vitro RNA pulldown or RNA-immunoprecipitation experiments in both ESCs and in vitro differentiated cardiac progenitor cells.…”
Section: Interactions With Histone Modifying Complexesmentioning
confidence: 99%